RESPONSE OF STABLE OVERALL SLOPE GEOMETRY OF OPEN PIT COAL MINE IN WARUKIN FORMATION TO DEWATERING AND PEAK GROUND SEISMIC IN SOUTH KALIMANTAN, INDONESIA - Oscar, Agus W; Muslim M.Sc., Ir. H. Dicky; Sulaksana, Nana; Hirnawan, Febri (Buletin Sumber Daya Geologi, 2016)
Understanding of the response of the mine slope stability is very important regarding the safety of life and investment / productivity / environment, as anticipation of landslide prevention based on the latest research. Mine slope behavior previously discussed widely in terms of the response due to dewatering and seismic (Peak Ground Acceleration) as well through verification. This paper aims to obtain a broad dimension of design criteria that are not only unstable slopes, but the slope is stable under various conditions of the rock mass saturation (dewatering) and seismic condition. Response of slope stability per geotechnical rocks unit from different formations or any engineering formation as a result of environmental influences, for example, the same quake, will be different. This means that the geometry of the same slope in other formation will have different stability conditions (safety factor of the slope) due to the same seismic acceleration. This is also similar due to dewatering. The method used for this study is the deductive-probabilistic method with a hypothetical verification approach. The Standard statistical analysis is used to test the data normality and homogeneity, average and independent differences, as well as regression-correlation test. The research results show that dewatering activitycan decrease ground water level (GWL/MAT) of the slope, so the durability of sliding along the sliding plane is reduced (increasing slope safety factor). At the same time earthquake reduces shear strength and increases driving force, so the safety factor of the slope suddenly downs. Slope stability decreased due to the earthquake, but dewatering improves slope stability. Thus, the slope in dewatering conditions will be kept stable through simulation to anticipate earthquake.